2018
DOI: 10.1371/journal.pone.0189993
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid genome assembly and annotation of Paenibacillus pasadenensis strain R16 reveals insights on endophytic life style and antifungal activity

Abstract: Bacteria of the Paenibacillus genus are becoming important in many fields of science, including agriculture, for their positive effects on the health of plants. However, there are little information available on this genus compared to other bacteria (such as Bacillus or Pseudomonas), especially when considering genomic information. Sequencing the genomes of plant-beneficial bacteria is a crucial step to identify the genetic elements underlying the adaptation to life inside a plant host and, in particular, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Nevertheless, with very limited information on its phosphatase enzymes, many strains of Paenibacillus sp. have been previously used as biofertilizer with a consortium of bacterial species and its functional traits was only based on its genome analysis (Khalid et al 2009;Shtark et al 2010;Passera et al 2018). Nevertheless, no studies have been reported on the catalytic and structural properties of phosphatase.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, with very limited information on its phosphatase enzymes, many strains of Paenibacillus sp. have been previously used as biofertilizer with a consortium of bacterial species and its functional traits was only based on its genome analysis (Khalid et al 2009;Shtark et al 2010;Passera et al 2018). Nevertheless, no studies have been reported on the catalytic and structural properties of phosphatase.…”
Section: Resultsmentioning
confidence: 99%
“…The terpene biosynthetic pathway is unknown in the genus Paenibacillus sp. The partial hypothetical pathway was proposed by Passera et al (2018) for Paenibacillus pasadenensis strain R16, which was reported to produce sesquiterpenoid farnesol. The antibacterial activities of sesquiterpenoids and different terpenes against Gram-positive and Gram-negative bacteria have been determined previously ( Mahizan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the genus Paenibacillus has recently been the subject of scientific reviews [1][2][3]. In an attempt to generate additional data on the relatively poorly understood Paenibacillus taxon, detailed studies have been performed to identify and characterize Paenibacillus isolates to facilitate their utilization [4,5]. In addition to the diverse beneficial Paenibacillus species, important pathogens of beneficial insects are also members of this genus [1,6].…”
Section: Introductionmentioning
confidence: 99%